Caracterización de cuatro métodos de beneficio para el análisis físico y sensorial de café robusta en el cantón Bolívar - Palma Lozano, Marcelo David (2023)
The purpose of this titling work consisted of comparing the methods of processing robusta coffee beans to determine their physical and organoleptic characteristics in Bolivar canton, for its execution 16 samples were taken from the semi-wet, enzymatic, wet and natural processing methods. A natural drying process was carried out until reaching a humidity index of 11 to 13% in accordance with the Ecuadorian Technical Standard INEN 285:2006, which establishes the classification and requirements for green coffee beans. For the evaluation of the physical and sensory analysis, the quality standards of the United States established by the SCAA (2015) were followed. In addition, the organoleptic analysis was measured on an ordinal scale from 0 to 10 where the Kruskal and Wallis statistical test of variance by ranks was used. The results showed that the mill that obtained the best result of the four methods according to the SCAA table was the enzymatic wet mill (BHE2) with a low value of 37 g of physical defects, while the wet mill (washed coffee) showed greater physical defects with 85 g, due to the fact that the sample presented a considerable amount of whole and partial sour beans, as well as black beans, broken, bitten and cut beans as a result of damage suffered during pulping. The cup profiles established that the four benefits presented a maximum score of 10 points in the uniformity and clean cup characteristics; while, for aroma, flavor, residual flavor, acidity, body and sweetness, they turned out to be statistically similar in the enzymatic, semi-wet, wet and dry processing methods.